Analysing the Source Text: A First Step for a Successful Translation - Claudia E. Stoian (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
The translation of pragmatic texts requires many skills, among which that of analysing the source text to be translated. The present paper proposes the functional analysis as a helpful approach for training translation and interpreting students into such skills. It focuses on register analysis, paying attention to field, mode and tenor, and puts forward several activities meant to develop and improve student’s abilities in understanding their texts as a first step in obtaining successful translations.